Change for Aptness: Fighting Flaws in the Federal Supreme Court Cassation Division - Bisrat Teklu; Debebe, Markos (Jimma University Journal of law, 2013)
The Federal Supreme Court Cassation Division is established with a view to guarding the legislature’s purpose and intent. However, at times, the Division deviates from what the law says and the law-maker intends even to the extent of twisting a clear provision of the law. This can be due to several reasons. This article articulates that in order to fight such flaws in the Cassation Division, it is important to constitute the Division into specialized divisions, employ legal assistants for each specialized Division, appoint an advisory board for specialized divisions, awakening the Judicial Administration Council and conducting detailed studies on the overall performance of the Division.